2006
DOI: 10.1128/aem.72.4.2936-2941.2006
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress, Temperature, and Inoculation Concentration Influence the Adhesion of Water-Stressed Helicobacter pylori to Stainless Steel 304 and Polypropylene

Abstract: Although molecular techniques have identified Helicobacter pylori in drinking water-associated biofilms, there is a lack of studies reporting what factors affect the attachment of the bacterium to plumbing materials. Therefore, the adhesion of H. pylori suspended in distilled water to stainless steel 304 (SS304) coupons placed on tissue culture plates subjected to different environmental conditions was monitored. The extent of adhesion was evaluated for different water exposure times, using epifluorescence mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 31 publications
2
50
0
1
Order By: Relevance
“…2,15,28,31 These compact devices, facilitate multi-sample testing, provide oscillatory fluid motion with adjustable speeds and do not require bulky pump-flow cell-tubing setups and problems associated with them in terms of manufacturing and sealing. Also, the relatively large and flat surfaces of each well provide easy access for optical measurements, microscopy and other analysis.…”
Section: Introductionmentioning
confidence: 99%
“…2,15,28,31 These compact devices, facilitate multi-sample testing, provide oscillatory fluid motion with adjustable speeds and do not require bulky pump-flow cell-tubing setups and problems associated with them in terms of manufacturing and sealing. Also, the relatively large and flat surfaces of each well provide easy access for optical measurements, microscopy and other analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For all strains, the number of culturable cells on the surface increased up to 10 4 to 10 6 CFU/cm 2 in the first 2 h due to the initial adhesion process. Even though it has been previously shown that the total number of cells adhered continues to rise until 48 h (3,5), culturable cell numbers started to decrease after only 2 hours (for polyvinyl chloride [PVC] and glass and strain J99, the numbers stabilized). This effect was partly expected, as the culturability time for H. pylori in water at this temperature is quite low (1, 4).…”
mentioning
confidence: 99%
“…Nevertheless, biofilms are prolific in microenvironments, and the possibility of areas where the bacterium survives cannot be excluded. Future work on screening different types of surface-related microenvironments will allow confirmation of hypotheses developed on the data already acquired on pure culture studies (3,5) and in developing new hypotheses. Finally, this study also brings new insights to the H. pylori transmission debate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Azevedo and colleagues [28] [44] [45] have worked with biofilms in pipes and water deposits, and they consider this to be the way bacteria can remain viable in the water. Additionally, biofilms developed by multiple H. pylori strains are, in general terms, more complex than those associated with single strains; such condition might promote the genetic exchange favoring the generation of more virulent strains [46].…”
Section: Discussionmentioning
confidence: 99%